2015
DOI: 10.1063/1.4905607
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent behavior of thermal conductivity of sub-5 nm Ir film: Defect-electron scattering quantified by residual thermal resistivity

Abstract: By studying the temperature-dependent behavior (300 K down to 43 K) of electron thermal conductivity () in a 3.2 nm-thin Ir film, we quantify the extremely confined defect-electron scatterings and isolate the intrinsic phonon-electron scattering that is shared by the bulk Ir. At low temperatures below 50 K,  of the film has almost two orders of magnitude reduction from that of bulk Ir. The film has ∂/∂T>0 while the bulk Ir has ∂/∂T <0. We introduce a unified thermal resistivity (=T/) to interpret these c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The same phonon scattering mechanism results in different influences on the electrical and thermal transport properties. For Ir films coated on milkweed floss, we have observed that the ∂Θ/∂ T and ∂ ρ e /∂ T of Ir film show the very similar deviation from bulk Ir 19 34 . Possible reasons for the very large difference in the thermal and electrical conduction of silver nanowire are the change of electron-phonon coupling strength induced by structural disorder and quantum size effect, and the change of phonon population and electronic structure which involves small and large angle scatterings 35 36 .…”
Section: Resultsmentioning
confidence: 77%
“…The same phonon scattering mechanism results in different influences on the electrical and thermal transport properties. For Ir films coated on milkweed floss, we have observed that the ∂Θ/∂ T and ∂ ρ e /∂ T of Ir film show the very similar deviation from bulk Ir 19 34 . Possible reasons for the very large difference in the thermal and electrical conduction of silver nanowire are the change of electron-phonon coupling strength induced by structural disorder and quantum size effect, and the change of phonon population and electronic structure which involves small and large angle scatterings 35 36 .…”
Section: Resultsmentioning
confidence: 77%
“…For metallic nanostructures, it still remains controversy whether Wiedemann-Franz law holds exactly. [25][26][27][28] Therefore, we deposited thick Al layer (218 nm) on the nucleation side by sputtering deposition and obtained high sensitivity for Al thermal conductivity. The Al thermal conductivity is fitted as 152 W/m-K by multi-frequency TDTR measurements and fixed in the subsequent anisotropy thermal model.…”
Section: Sample Description and Characterizationmentioning
confidence: 99%
“…The measurement accuracy has been fully evaluated by measuring reference materials and comparing the results with reference values. More details could be found in the references. ,, …”
Section: Thermal Conductivity Of Uhmwpementioning
confidence: 99%